2018
DOI: 10.1186/s12944-018-0820-7
|View full text |Cite
|
Sign up to set email alerts
|

Does supplemental zeolite (clinoptilolite) affect growth performance, meat texture, oxidative stress and production of polyunsaturated fatty acid of Turkey poults?

Abstract: BackgroundFollowing the ban on the use of growth factors, the use of zeolite in poultry feed could be a solution to obtain healthier food products that are more demanded by the consumer.MethodsZeolite (Clinoptilolite) was added to turkey male and female feed at concentrations 1% or 2% and was evaluated for its effectiveness on performance of the production. The turkeys were given free and continuous access to a nutritionally non-limiting diet (in meal form) that was either a basal diet or a ‘Zeolite supplement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 52 publications
(55 reference statements)
1
28
0
Order By: Relevance
“…Lipid oxidation is an important factor affecting the sensory and nutritional value, safety, and shelf life of animal products [19]. The MDA level is an important and significant biomarker of oxidative stress and lipid oxidation [7]. The effects of stunning methods on lipid oxidation in the liver of geese are shown in Table 2.…”
Section: Lipid Oxidative Stabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Lipid oxidation is an important factor affecting the sensory and nutritional value, safety, and shelf life of animal products [19]. The MDA level is an important and significant biomarker of oxidative stress and lipid oxidation [7]. The effects of stunning methods on lipid oxidation in the liver of geese are shown in Table 2.…”
Section: Lipid Oxidative Stabilitymentioning
confidence: 99%
“…Lipid oxidation refers to the reactive oxygen species, which exceeds the ability of a system to neutralize and eliminate them [5]. Lipid oxidation can lead to unpleasant odors or tastes, color deteriorations, degradation in proteins, and decline in the shelf life of food [6,7]. The factors that affect lipid oxidation in poultry products include poultry diet, oxidative stresses in the live birds, pre-slaughter stunning methods, food processing methods, and storage conditions [8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Increased PUFA might decrease the hardness and thus promote improvements in the texture of the egg yolk. Although there have been no previous reports on egg texture changes by PUFA, research into meat quality has suggested that higher levels of PUFA increase its chewiness and meat texture ( Hcini et al., 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Also, clinoptilolite improve antioxidant capacity in broilers [74]; it is used as a feed additive in fish diets [75] and in turkey diets [76].…”
Section: Effects On Health Status and Growth Performancementioning
confidence: 99%